THE INFLUENCE OF PERTURBATION PAIRWISE COMPARISON MATRIX ON THE CONSISTENCY RATIO AND RANK REVERSAL IN THE ANALYTIC HIERARCHY PROCESS (AHP) - HAFIYUSHOLEH (NIM: 20107033), MOH.
This project studies a pairwise comparison matrix (PC) used to construct a model of a decision making that known as Analytic Hierarchy Process (AHP). AHP is a method of decision making which is based on a multi criteria. One of the methods used to obtain priority vectors in AHP is the eigenvalue method. The consistency of the corresponding matrices is one of important component in supporting a valid decision. This project will discuss the effect of disturbance to the consistency ratio of the perturbed pairwise comparison matrix. It will also discuss the behavior of priority vector of the perturbed pairwise comparison matrix. Particularly it is investigated disturbances causing rank reversal.